AN ANALYSIS OF DIRECTIVE SPEECH ACTS PRODUCED BY TEACHERS IN EFL CLASSROOM - Putu Dinia Suryandani; I Gede Budasi (Universitas Bunda Mulia, 2021)
The teaching and learning process entails several encounters in which the teacher and students exchange a variety of utterances, particularly in language classes. Understanding language involves an understanding of pragmatics. Teaching and learning will be more successful if appropriate speech acts are used. Directive Speech Acts are a type of speech act that is frequently employed in classroom interactions. It is used by the teacher to give instruction, command the students to do something, limit the students’ bad behavior, etc. This study aims at investigating the types of directive speech acts and analyzing the functions of the acts used by English teachers at SMKN 1 Sawan. The theory of directive acts classification adopted in this study is the theory proposed by Ibrahim (1993). Ibrahim’s theory classified directive acts into six major types. They are requestive, question, requirement, prohibitive, permission and advisory. This research also focused on the functions of directive acts based on Amalsaleh, Yamini, and Yarmohammadi's (2004) theory. They are elicitation, instruction, advice, threat, and attention-getter. This research was a descriptive study with two teachers as the subjects of this research. Observation and recording were used as the technique in collecting the data. The validity of the data used is source and theory of triangulation. The results showed that the most frequent type of directive speech acts used by the teachers was question directive with occurance of 185 utterances (46.95%). Teachers that employ the question directive encourage students to be interested in the world around them, to enhance their abilities and attitudes toward science, and to enhance their speech communication and critical thinking. The other functions of the acts were also identified in various types of the acts.